Resonance ghost anomaly of the ⁸Be nucleus in reactions ¹²C(γ, 3α), ¹²C(γ, n)3He2α and ¹²C(γ, p)3H2α - Afanas'ev, S.N.; Gushchyn, D.V.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2009)
On the excitation curve for a system of two 2α-particles in the reactions ¹²C(γ, 3α), ¹²C(γ, n)3He2α and ¹²C(γ, p)3H2α, a resonance structure with a maximum located at E0 = 0.72 MeV and width G ~ 0.75 MeV is found between the maxima corresponding to the ground and the first excited state of the ⁸Be nucleus, and identified as a ghost anomaly (GA). The GA are explanation in the framework of the R-matrix theory of nuclear reactions. У кривій збудження 2α-системи в реакціях¹²C(γ, 3α), ¹²C(γ, n)3He2α і ¹²C(γ, p)3H2α між основним і першим збудженим станами ядра ⁸Be виявлено резонансну структуру з максимумом E0 = 0.72 МеВ і шириною G ~ 0.75 МеВ, ідентифіковану як аномалія-примара (АП). Характеристики АП пояснені в рамках R-матричної теорії ядерних реакцій. В кривой возбуждения 2α-системы в реакциях¹²C(γ, 3α), ¹²C(γ, n)3He2α и ¹²C(γ, p)3H2α между основным и первым возбужденным состояниями ядра ⁸Be обнаружен резонанс с максимумом E0 = 0.72 МэВ и шириной G ~ 0.75 МэВ, идентифицированный как аномалия-призрак (АП). Характеристики АП объяснены в рамках R-матричной теории ядерных реакций.